Torque depression following active shortening is associated with a modulation of cortical and spinal excitation: a history‐dependent study - Grant, Jordan (Physiol Rep, 2017)
The reduction in steady‐state isometric torque following a shortening muscle action when compared to a purely isometric contraction at the same muscle length and level of activation is termed torque depression (TD). The purpose of this study was to investigate spinal and supraspinal neural responses during the TD state of a maximal voluntary activation of the ankle dorsiflexors. Thirteen subjects (10 male) were recruited for the study. To explore alterations in corticospinal excitability during voluntary muscle activation in the TD state, motor evoked potentials (MEPs), cervicomedullary motor evoked potentials (CMEPs), and maximal compound muscle action potentials (Mmax) were elicited during the isometric steady‐state following active shortening (i.e., TD) and the purely isometric condition. A 15% reduction in steady‐state isometric torque (P < 0.05) was observed following isokinetic shortening at 40°/sec. Although mean evoked responses (MEP and CMEP) were not different in the TD state as compared with purely isometric state, the changes in evoked responses were inversely related to one another depending on the level of TD. These findings indicate that supraspinal and spinal responses are interrelated in the TD state. Furthermore, antagonist muscle coactivation during the isometric reference contraction was positively related to TD. These findings suggest the possibility of a relationship between the central nervous system and TD in humans. Further work should be performed to definitively link TD to specific spinal interneurons.